L-fucose from vitamin C with only acetonide protection. - Liu, Z; Yoshihara, A; Wormald, MR; Jenkinson, S; Gibson, V; Izumori, K; Fleet, G (American Chemical Society, 2014)
Addition of human milk oligosaccharides (HMO) to baby foods may protect infants from disease. As many simple HMOs are fucosylated this is likely to increase the demand for L-fucose as a synthetic building block. Any chemical synthesis must be cheap to compete with a biotechnological process. Acetonide is the only protecting group we have used in this new synthesis of L-fucose from vitamin C in 27% overall yield (purification by recrystallization; no chromatography required in the entire sequence).